Drift instability in the presence of a ac electric field - Misra K.D.; Tiwari M.S. (My University, 2025)
The dispersion relation and the growth rate of the drift wave in an inhomogeneous plasma in the presence of ac electric field applied perpendicular to the impressed magnetic field, have been obtained by investigating the trajectories of the charged particles and the wave particle energy exchange method. The general dispersion relation for the electrostatic drift wave has been obtained. It is found that when a low frequency ac electric field less than the ion cyclotron frequency is applied in the presence of a weak magnetic field, then it significantly modifies and enhances the growth rate. Frequencies higher than the ion cyclotron frequency do not affect the growth rate for a weak applied electric field. At higher frequencies high order of electric fields are required to excite the wave. Frequencies higher than 500 Hz do not show any significant deviations in ω vs k⊥ diagram for the assumed space plasma parameters. Application of these results have been made for the ionospheric plasma. A dispersion relation has also been calculated for the laboratory plasma. © 1980.